A Prototype of Web-Based Simulation Environment (WEBSIM) - Tan, Kee Leong (2000)
Computer simulation is the discipline of designing a model of an actual or theoretical physical system, executing the model on a computer, and analysing the execution output. Among the popular simulation tools are Mil3 Opnet, Mathworks MATLAB and even self-developed simulation program (using language such as Pascal, Fortran and C/C++). However, these simulation tools have limitations such as platform dependent, expensive cost, maintenance difficulties and limited in reusability. One of the methods to overcome this limitation is by implementing web-based simulation. Web-based simulation allows simulation to be carried out over the Internet using a standard web browser. The usage of web browsers make the Internet a very user-friendly environment by integrating all related resources into a single tool that eliminates the steep learning curve for novice simulation users. In this thesis, we present the web-based simulation environment project (Websim). Websim uploads a simulation program (developed using C/C++) in binary format, generates a web-interface for the program and allows users to access the simulation program y 1<1 the Internet. The results generated from the simulation program would be translated into an image file. Finally, the Image file is embedded into an HTML file, and returned to Websim users. Websim is mainly developed using the combination of CGI and Javascript technologies. The server-side CGI scripts, written in Perl process the various requests from users, while the chent-side Javascript is used to perform user inputs validations. Thus, lessen the workload of the server and tighten the security. Websim is able to receive the simulation program m executable format and provide a web interface for it. This gives the flexibility and convenience of using the programming language of choice for the simulation modeller, and to integrate it with the web. Besides that, Websim also allows the storage of simulation program on a web server, thus could act as an online store for simulation programs. This permits the sharing of simulation program over the Internet, to an exclusive user groups or to the general public. Finally, Websim could act as a teaching tool in school and universities, especially for courses involving modelling and simulation. It allows teaching and learning to be done through the Internet, hence could assist students in having a better understanding on certain topics or concepts.